The Medicinal Chemistry of Therapeutic Peptides: Recent Developments in Synthesis and Design Optimizations - Parthasarathy, Anutthaman; Anandamma, Sasikala K.; Kalesh, Karunakaran A. (Current Medicinal Chemistry, 2019)
Peptide therapeutics has made tremendous progress in the past decade. Many of the inherent weaknesses of peptides which hampered their development as therapeutics are now more or less effectively tackled with recent scientific and technological advancements in integrated drug discovery settings. These include recent developments in synthetic organic chemistry, high-throughput recombinant production strategies, highresolution analytical methods, high-throughput screening options, ingenious drug delivery strategies and novel formulation preparations. Here, we will briefly describe the key methodologies and strategies used in the therapeutic peptide development processes with selected examples of the most recent developments in the field. The aim of this review is to highlight the viable options a medicinal chemist may consider in order to improve a specific pharmacological property of interest in a peptide lead entity and thereby rationally assess the therapeutic potential this class of molecules possesses while they are traditionally (and incorrectly) considered ‘undruggable’.
Keywords: high-throughput screening